Leadership Communication Role within International Business Organization - Křetínská, Tereza; Čejka, Pavel; Vysoká škola ekonomická v Praze. Fakulta managementu; Matoušek, David (2015)
The thesis focuses on the role of leadership communication within a multinational business organization. It aims to confirm the critical importance of communication provided by leaders to their team members. The literature review will focus on the existing communication flows within organizations and the current research results and insights in the field of leadership communication, which is a new, emerging domain of study. Thanks to recent quantitative research (Men, 2014b), it has been already confirmed that leadership communication has a direct effect on employee-organization relationships and overall internal communication. However, qualitative research has been suggested for validation of how the discovered model works in concrete environments (Men, 2014b). Thus, the research section will reveal the findings of in-depth semi-structured interview analysis within a global internal IT services provider which is part of a Group enterprise operating in the logistics industry world-wide. The thesis will culminate in defining logical reasoning for adding communication skills to the company's core competencies for organizational managers and leaders.
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2015
Vedoucí práce: Pavel Čejka
Obsahuje bibliografii
Rok obhajoby 2015
Keywords: management; řídící práce; mezinárodní komunikace; management [obor dipl. práce]; diplomové práce; management; leadership; international communication; master's theses